2001
DOI: 10.1182/blood.v97.10.2998
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison between rasburicase and allopurinol in children with lymphoma or leukemia at high risk for tumor lysis

Abstract: Standard therapy in the United States for malignancy-associated hyperuricemia consists of hydration, alkalinization, and allopurinol. Urate oxidase catalyzes the enzymatic oxidation of uric acid to a 5 times increased urine soluble product, allantoin. Rasburicase is a new recombinant form of urate oxidase available for clinical evaluation. This multicenter randomized trial compared allopurinol to rasburicase in pediatric patients with leukemia or lymphoma at high risk for tumor lysis. Patients received the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
305
3
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 419 publications
(326 citation statements)
references
References 15 publications
9
305
3
9
Order By: Relevance
“…Similarly, a randomized study of rasburicase and allopurinol in children showed faster decline in uric acid with rasburicase therapy without any obvious short-term survival advantage for rasburicasetreated patients. 6 A European multi-center study of rasburicase in 100 patients with aggressive NHL -only 11% of whom were hyperuricemic -found normalization of serum uric acid levels within 4 h of the first dose. 7 The dose of rasburicase used in the study was 0.2 mg/kg daily for 3-7 days (median 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, a randomized study of rasburicase and allopurinol in children showed faster decline in uric acid with rasburicase therapy without any obvious short-term survival advantage for rasburicasetreated patients. 6 A European multi-center study of rasburicase in 100 patients with aggressive NHL -only 11% of whom were hyperuricemic -found normalization of serum uric acid levels within 4 h of the first dose. 7 The dose of rasburicase used in the study was 0.2 mg/kg daily for 3-7 days (median 3).…”
Section: Discussionmentioning
confidence: 99%
“…6,7,11 It should be noted that in the United States, rasburicase is approved for therapy only in children. Therefore, there is no recommended dose for adults who may require it under appropriate clinical circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rasburicase catalyses the conversion of poorly soluble uric acid into allantoin, which is five to ten times more soluble in urine as compared to uric acid and can be easily excreted by kidneys (Cheson and Dutcher, 2005;Cammalleri and Malaguarnera, 2007;Zojer and Ludwig, 2007). In general, response to rasburicase is rapid and the treatment is well tolerated (Goldman et al, 2001;Patte et al, 2002;Bosly et al, 2003;Coiffier et al, 2003). In patients at highest risk of developing TLS, rasburicase is generally recommended as the preferred prophylaxis (Cairo and Bishop, 2004;Cairo et al, 2007;Zojer and Ludwig, 2007;Mayne et al, 2008).…”
Section: Treatment With Allopurinol and Rasburicasementioning
confidence: 99%